1999
DOI: 10.1111/j.1572-0241.1999.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Endoscopic Drainage of Pancreatic Pseudocysts

Abstract: Transmural endoscopic drainage is a safe procedure with minimal complications. It should be the procedure of choice for pseudocysts associated with chronic pancreatitis or trauma, with a wall thickness of < 1 cm and a visible bulge into the gastrointestinal lumen. Forty percent of pseudocysts fulfilled these criteria in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 21 publications
1
78
0
10
Order By: Relevance
“…A etiologia mais freqüente dos pseudocistos é atribuída à pancreatite crônica alcoólica (2,4,11,14,17,20) e entre os sinais e sintomas observados predominam a massa abdominal palpável e a dor em andar superior do abdome (3,10) . A etiologia predominante, no entanto, pode variar em função de peculiaridades da casuística.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A etiologia mais freqüente dos pseudocistos é atribuída à pancreatite crônica alcoólica (2,4,11,14,17,20) e entre os sinais e sintomas observados predominam a massa abdominal palpável e a dor em andar superior do abdome (3,10) . A etiologia predominante, no entanto, pode variar em função de peculiaridades da casuística.…”
Section: Discussionunclassified
“…Segundo alguns autores a drenagem transmural, principalmente a cistogastrostomia, apresenta elevados riscos de complicações, especialmente sangramento (13,20) . BECKINGHAM et al (3) referiram hemorragia em 11,7% (4/34) dos pacientes, sendo que 1 foi submetido a cirurgia de urgência para coibir o sangramento. Esses autores realizavam cistoenterostomias amplas, através da utilização de papilótomos de 10 mm para permitir ampla drenagem, aumentando assim, em nosso entendimento a probabilidade de hemorragias.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Long-term results of transmural drainage are not well-known, follow-up not exceeding 31 mo. A recent study including 34 patients followed 46 mo, reported good results in 62% of cases (in intent to treat) with only 71% of initially technical success [54] . Three cases of recurrence were reported, of whom two cases were successfully managed endoscopically.…”
Section: Treatment Of Pancreatic Cysts and Pseudo Cystsmentioning
confidence: 99%
“…Large (≥6cm diameter), persistent (≥6 weeks), and symptomatic pseudocysts are indications for drainage, which is best achieved endoscopically or surgically (Ammori & Baghdadi, 2006). Endoscopic transmural (transgastric or transduodenal) drainage may be possible in some patients with pancreatic pseudocysts, and is best reserved for pseudocysts that complicate chronic pancreatitis (rather than acute pancreatitis) in the head or body of the pancreas, and those with a wall thickness of less than 1cm (Beckingham et al, 1999). Surgery remains the gold standard for the management of large, persistent and recurrent pseudocysts.…”
Section: Laparoscopic Application To Pancreatitismentioning
confidence: 99%